(untitled) (Research, Society and Development, 2021)
This study aims to describe experiences of actions aimed at adults in poor communities in the city of Patos, Paraíba. The applied methodology refers to an experience report of students in Dentistry at the Federal University of Campina Grande (UFCG), campus of Patos, Paraíba. Members linked to a University Extension (PROBEX) entitled: Human Freshers Program - Promoting Oral Health in the Pastoral da Criança. Calouros has eighteen extension participants, four coordinating teachers, as well as students from the first period of Dentistry classes. The actions were carried out in partnership with the Pastoral da Criança of the diocese of Patos. The scope of the project took place during the current year, nine actions were carried out in the most diverse districts of Patos, these presenting little or no access to basic education on oral health. The results correspond to the disseminated knowledge that took place in the form of a lecture with banners and conversation circles, the communication took place in a simple way for a better understanding and access for all, with basic knowledge and easy daily execution. We concluded that the project complemented and reached the importance of the dissemination of basic oral health care, being also significant in reaching the population at risk and with little access to information.